A origem do parlamentarismo e algumas de suas manifestações históricas no Brasil - Rocha Filho, Roberto de Carvalho (2003)
The main goal of this master' s degree thesis is to examine the origin of the parliamentary system of govemment in England, as well as to give a historical account of how this idea spread out in Brazil, by emphasizing its importance for the consolidation of democracy. This thesis deals with constitutional law matters, ranging from moral, psychological, historical and philosophical aspects to economic, sociological and poli tical features which were relevant for the growing and development of both the English and the Brazilian nations. Furthermore, it points out that in the 50's Raul Pilla defended and condensed the parlamentarian ideas in a very successfull way, while Afonso Arinos did the same with similar brilliance concerning the presidential system's conception. As for the 60's, this thesis aims at analysing the causes of the failure of João Goulart's parliamentarian govemment in Brazil. In this historical context, it also covers a description of the different ideas represented by both the presidential and the parliamentary systems of govemment, as well as by both the republican and the monarchical forms of govemment, which got to become current again in Brazil during the plebiscitary year of 1993. In its conc1usive part, this thesis shall broach the origins of social discrimination in Brazil, name1y slavery and colonialism. These inherited problems could be better prevented from if one could count on an effective parliamentarian system, for such a democratic system is not compatible with the injustice generated within institutions by authoritarianism.